Effect of EDM process parameters on material removal rate and surface roughness of metal matrix composites: A review. (2020) - Dinesh Kumar, S.; Ravichandran, M.; Alagarsamy, S.V.; Meignanamoorthy, M.; Sakthivelu, S.
Abstract: Electric erosion process is generally used for processing the metal matrix composites which have more applications in aerospace, aircraft and automobile sectors. Metal Matrix composites have attractive physical and mechanical properties like light weight, high specific modulus, highest strength and thermal stability. The present review is discussed about Electric erosion process and its input and output parameters such as Pulse on time, Pulse off time, Current, etc. on the material removal rate and surface roughness of the composites. This review paper also address the principle of electric erosion process and the impact of the surface properties of the processed composites.